Design of a profilograph for mapping pavement in virtual environment - Khan, Md. Raisuddin; Billah, Md. Masum; Ahmed, Mohiuddin (IEEE, 2012)
In this paper, a novel profilograph has been designed and implemented to generate virtual terrain. Profilograph is necessary for civil engineering applications to map pavement smoothness. Traditional profilographs are big in size and take long time for mapping, although they are capable of generating pavement map but unable to show 3D graph. The profilograph proposed in this paper is able to map pavement smoothness faster as well as show 3D graphs of the pavement. This profilograph consists of two subsystems. The first subsystem is a hardware system designed using rate gyros and accelerometers with some wireless communicating module. Another subsystem is the software system developed using OpenGL with supported of C++ and Visual Basic. This software can be connected with the hardware system either using wire or using wireless. The hardware system while driven on the pavement stores the data of the terrain into the database. The software generates 3D graphs of the navigated terrain. This profilograph can be used not only in civil engineering pavement mapping but also in mapping disaster scenario for disaster rescue missions.